Reproductive biology of Elymus scabrifolius (Döll) J. H. Hunz. (Poaceae: Triticeae), an important phytogenetic resource for saline environments - Richard, Geraldina Alicia (2024)
Ten plants per population (Table 1) were observed (n = 10 plants per population) twice a week. To obtain the number of flowering days per population, for each plant, the date of the beginning of flowering (when the first spike presented at least one open floret) and the date of the end of flowering (when the last flowering spike presented more than 50% open florets) were recorded.